The essence of interethnic processes and some remarks on their evolutionary perfection - Nasriddin Ataqulovich, Nazarov; Nizomiddin Sheralievich, Berdaliev; Ajimuratovich, Utemuratov Mahmut; Ajimuratovich, Rashidova Mashkhura (International Journal of Psychosocial Rehabilitation, 2020)
This article focuses on the essence of interethnic processes, the stages of formation and development of ethnos. The role of the concepts of ethnic group, subetnos, Ethnos, nation, microetnos and macroetnos in national-ethnic theories is analyzed and the essence of the categories of diaspora and irredenta is revealed on the basis of concrete examples. Touching upon the issues of Ethnos and nationalities in detail, scientific conceptions in this regard are analyzed, they are categorized in terms of content and essence. It is emphasized that the emphasis on the essence of interethnic processes and the proposition of proposals and recommendations on the optimal essence of the development of processes is a factor that ensures the national development of each society. The term Ethnos is based on the commonality of aspects of a particular language, tradition, habit, national selfawareness, the fact that this unit is basically a concept that represents the theoretical, demos, that is, the term folk is actively used in popular publications and in all spheres of social life, in addition to scientific literature, and its use as a synonym for the term Ethnos, as well as in relation to the people of a particular territory or country, is analyzed on theoretical basis.